2014
DOI: 10.1111/jpm.12170
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stressors, burnout and coping strategies between hospital and community psychiatric nurses in a Dublin region

Abstract: Burnout negatively impacts the delivery of mental health services. Psychiatric nurses face stressors that are distinct from other nursing specialities. The research was conducted in Ireland and captured a relatively large sample of respondents. The results compared the stressors, coping strategies and burnout levels between hospital and community-based psychiatric nurses. Occupational stress can negatively impact on the well-being of psychiatric nurses, which in turn can lead to poor client care. There is a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
5
18

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 66 publications
13
92
5
18
Order By: Relevance
“…Both groups showed average levels of emotional burnout, low levels of depersonalization, and average levels of personal fulfillment. (5) The work overload generates dissatisfaction with work and the profession, and may lead nursing professionals to think of changing jobs or even professional activity. (4) There is evidence that this occurs more frequently with nurses working in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both groups showed average levels of emotional burnout, low levels of depersonalization, and average levels of personal fulfillment. (5) The work overload generates dissatisfaction with work and the profession, and may lead nursing professionals to think of changing jobs or even professional activity. (4) There is evidence that this occurs more frequently with nurses working in hospital environments.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that professionals working in hospitals had higher scores of depersonalization and nurses working in community services had a greater sense of personal fulfillment. (5)(6)(7)(8)(9)(10)(11)(12) The exposure to conflict situations and living with violence in the workplace can contribute to the psychological burden on nursing professionals. A protective measure against the violence of patients can be implemented by the service management with appropriate therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research [13] conducted with 69 psychiatric nurses working in a hospital service to the Irish community revealed that the main causes of burnout were lack of resources, workload and organizational/process structures.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, McTiernan and McDonald [56] indicated that psychiatric nurses employ diverting attention and positive attitudes toward work strategies in coping with their daily work stressors. Also, Gholamzadeh, Sharif, and Dehghan Rad [57] reported that most nurses are trying to gain adaptation with their work tensions by believing in and feeling good about themselves; increasing knowledge and experience and relying on their abilities.…”
Section: Mean Sd the Most Used Coping Strategiesmentioning
confidence: 99%